Clinical Isolates of Human Coronavirus 229E Bypass the Endosome for Cell Entry - Shirato, Kazuya; Kanou, Kazuhiko; Kawase, Miyuki; Matsuyama, Shutoku (Journal of virology, 2017)
Human coronavirus 229E (HCoV-229E), a causative agent of the common cold, enters host cells via two distinct pathways: one is mediated by cell surface proteases, particularly transmembrane protease serine 2 (TMPRSS2), and the other by endosomal cathepsin L. Thus, specific inhibitors of these proteases block virus infection. However, it is unclear which of these pathways is actually utilized by HCoV-229E in the human respiratory tract. Here, we examined the mechanism of cell entry used by a pseudotyped virus bearing the HCoV-229E spike (S) protein in the presence or absence of protease inhibitors. We found that, compared with a laboratory strain isolated in 1966 and passaged for a half century, clinical isolates of HCoV-229E were less likely to utilize cathepsin L; rather, they showed a preference for TMPRSS2. Two amino acid substitutions (R642M and N714K) in the S protein of HCoV-229E clinical isolates altered their sensitivity to a cathepsin L inhibitor, suggesting that these amino acids were responsible for cathepsin L use. After 20 passages in HeLa cells, the ability of the isolate to use cathepsin increased so that it was equal to that of the laboratory strain; this increase was caused by an amino acid substitution (I577S) in the S protein. The passaged virus showed a reduced ability to replicate in differentiated airway epithelial cells cultured at an air-liquid interface. These results suggest that the endosomal pathway is disadvantageous for HCoV-229E infection of human airway epithelial cells; therefore, clinical isolates are less able to use cathepsin. IMPORTANCE Many enveloped viruses enter cells through endocytosis. Viral spike proteins drive the fusion of viral and endosomal membranes to facilitate insertion of the viral genome into the cytoplasm. Human coronavirus 229E (HCoV-229E) utilizes endosomal cathepsin L to activate the spike protein after receptor binding. Here, we found that clinical isolates of HCoV-229E preferentially utilize the cell surface protease TMPRSS2 rather than endosomal cathepsin L. The endosome is a main site of Toll-like receptor recognition, which then triggers an innate immune response; therefore, HCoV-229E presumably evolved to bypass the endosome by entering the cell via TMPRSS2. Thus, the virus uses a simple mechanism to evade the host innate immune system. Therefore, therapeutic agents for coronavirus-mediated diseases, such as severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS), should target cell surface TMPRSS2 rather than endosomal cathepsin.